Two new species of the springtail genus Ceratophysella Börner, 1932 from the Caucasus (Collembola: Hypogastruridae) - Babenko, Anatoly; Antipova, Maria (Zootaxa, 2025)
Two new species of the genus Ceratophysella Börner, 1932 are described from the Caucasus and Transcaucasia: C. dobrolyubovae sp. nov. and C. anacopica sp. nov. Both these species belong to the denticulata-group and are characterised by the fine and almost uniform cuticular granulation and relatively short dorsal setae. The former species from the mountainous Caucasian regions shows a complete set of papillae on the labium and only six dental setae, while the latter, inhabiting coastal communities, lacks labial papillae C, but has a complete set of seven dental setae. Additionally, molecular data for the cytochrome c oxidase subunit I gene (COI) were obtained for C. dobrolyubovae sp. nov. from four localities across the Caucasus. The first barcode sequences for C. caucasica Martynova, 1971 are also provided.